LIGHT DETECTION APPARATUS AND IMAGE RECONSTRUCTION METHOD USING THE SAME (2015)
A light detection apparatus and an image reconstruction method using the light detection apparatus are provided. The light detection apparatus includes a detection module and a control module. The detection module has a plurality of light detection units to constitute a hexagonal or honeycomb array structure. Each of the light detection units has a light-emitting element and a photosensitive element. The control module has a selector and a multiplexer. The selector selects at least one light-emitting element to produce a light source, so as to emit a plurality of photons to an object-under-test. The multiplexer selects at least one photosensitive element to detect light signals of the photons diffused to the object-under-test. The invention can obtain more light signals from the object-under-test to reconstruct images of the object-under-test.